Etnografi Virtual tentang Proliferasi Pemakaian Lagu “Bertaut” Karya Nadin Amizah di Media Sosial - Endah Murniaseh; Catur Suratnoaji; Heidy Arviani; Zainal Abidin Achmad (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
Linked song is experiencing widespread usage proliferation on social media. Social media users also benefit from using the Linked song elements, in the form of significant additions of viewers, followers, likes, and subscribers so that they get income from advertising. This study aims to investigate the forms of proliferation of “Bertaut” song use by Nadin Amizah on TikTok, YouTube, and Instagram. The research method uses a qualitative approach with virtual ethnography. The results of the study show that the proliferation of Bertaut songs occurs in various forms of content upload, including: song covers, stories, feeds, IGTV, footage, captions using song elements in the form of lyrics, music sound fragments, and song video fragments. The phenomenon of the proliferation of Linked songs on social media shows the media making capabilities of TikTok, YouTube, and Instagram